Chondrogenic potential of two hASCs subpopulations loaded onto gellan gum hydrogel evaluated in a nude mice model - Rada, Tommaso (2013)
Cells constitute one of the fundamental components of any cartilage tissue engineering approach. Adipose tissue derived stem cells (ASCs) have a promising future considering the abundance of this tissue in the human body, ease of harness, and the high number of stem cells that can be isolated from small amounts of tissue. However the stromal vascular fraction of the adipose tissue that is isolated upon digestion by collagenase followed by a rough selection of the adherent cells, is composed of many different types of cells, some of which may compromise the proliferation and the differentiation of the ASCs. This manuscript reports a study on the in vivo chondrogenic potential of two ASCs specific subpopulations isolated using a method based on immunomagnetic beads coated with specific antibodies. These ASCs subpopulations, isolated using immunomagnetic beads coated with CD29 and CD105 antibodies, were subsequently transfected with green fluorescent protein (GFP), expanded, and in pre-differentiated into the chondrogenic lineage, before being encapsulated in a novel hydrogel based on gellan gum, that has recently showed to promote in vitro and in vivo cartilage tissue formation. The two ASCs subpopulations encapsulated in the gellan gum hydrogel and in vitro predifferentiated, were then subcutaneously implanted in nude mice for 6 weeks. Explants were analyzed by various techniques, namely histology, immunohistology and real time RT-PCR that demonstrated the different behaviour of the two ASCs subpopulations under study, namely their potential to differentiate into the chondrogenic lineage and to form new cartilage tissue.